Greater admissions, mortality and cost of heart failure in adults with congenital heart disease. Issue 10 (23rd December 2020) - Burstein, Danielle S; Rossano, Joseph W; Griffis, Heather; Zhang, Xuemei; Fowler, Rachel; Frischertz, Benjamin; Kim, Yuli Y; Lindenfield, JoAnn; Mazurek, Jeremy A; Edelson, Jonathan B; Menachem, Jonathan N
Abstract : Objective: Limited contemporary data exist regarding outcomes and resource use among adults with congenital heart disease and heart failure (ACHD-HF). This study compared outcomes, emergency department (ED) and hospital resource use, and advanced heart failure (HF) therapies in ACHD-HF versus non-ACHD with HF (HF-non-ACHD). Methods: The Nationwide Emergency Department Sample and Nationwide Inpatient Sample were used to analyse outcomes and resource use among ACHD-HF ED visits and hospitalisations from 2006 to 2016. ACHD-HF was stratified by single-ventricle (SV) and two-ventricle (2V) disease. Results: A total of 76 557 ACHD-HF visits (3.6% SV physiology) and 31 137 414 HF-non-ACHD visits were analysed. ACHD-HFs were younger (SV 33 years (IQR 25–44), 2V 62 years (IQR 45–76); HF-non-ACHD 74 years (IQR 63–83); p<0.001). ACHD-HFs had higher ED admissions (78% vs 70%, p<0.001), longer hospital length of stay (5 days (IQR 2–8) vs 4 days (IQR 2–7), p<0.001) and greater hospital costs ($49K (IQR 2K–121K) vs $32K (17K–66K), p<0.001). Mortality was significantly higher among ACHD-HFs with SV physiology (6.6%; OR 1.6, 95% CI 1.1 to 2.3) or 2V physiology (6.3%; OR 1.4, 95% CI 1.3 to 1.5) versus HF-non-ACHD (5.5%). ACHF-HF hospitalisations increased more (46% vs 6% HF-non-ACHD) over a 10-year period, but the proportion receiving ventricular assist device (VAD) (ACHD-HF −2% vs HF-non-ACHD 294%) or transplant (ACHD-HF −37% vs HF-non-ACHD 73%) decreased. Conclusion: ACHD-HFs have significant ED and hospital resource use that has increased over the past 10 years. However, advanced HF therapies (VAD and transplantation) are less commonly used compared with those without adult congenital heart disease.